2017
DOI: 10.1111/1462-2920.14004
|View full text |Cite
|
Sign up to set email alerts
|

Localized high abundance of Marine Group II archaea in the subtropical Pearl River Estuary: implications for their niche adaptation

Abstract: Marine Group II archaea are widely distributed in global oceans and dominate the total archaeal community within the upper euphotic zone of temperate waters. However, factors controlling the distribution of MGII are poorly delineated and the physiology and ecological functions of these still-uncultured organisms remain elusive. In this study, we investigated the planktonic MGII associated with particles and in free-living forms in the Pearl River Estuary (PRE) over a 10-month period. We detected high abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 120 publications
(177 reference statements)
2
62
3
Order By: Relevance
“…Cluster 3, which was relatively more abundant in the surface and DCM, co-occurred with a catalase gene previously seen on MGII contigs (Tully, Sachdeva, Graham, & Heidelberg, 2017;Xie et al, 2018). The presence of a catalase gene suggests that some MGII have to deal with oxidative stress associated with phototrophs that produce reactive oxygen species (Xie et al, 2018).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Cluster 3, which was relatively more abundant in the surface and DCM, co-occurred with a catalase gene previously seen on MGII contigs (Tully, Sachdeva, Graham, & Heidelberg, 2017;Xie et al, 2018). The presence of a catalase gene suggests that some MGII have to deal with oxidative stress associated with phototrophs that produce reactive oxygen species (Xie et al, 2018).…”
Section: Discussionmentioning
confidence: 66%
“…Another study separated five different subclades of MGII proteorhodopsin (Tully, 2019) following nomenclature from (Boeuf, Audic, Brillet-Guéguen, Caron, & Jeanthon, 2015;Pinhassi, DeLong, Béjà, González, & Pedrós-Alió, 2016). Other metagenomics fragments suggest that some MGIIa could live associated to particles, and that they could be motile and degrade polymers like proteins and lipids (Iverson et al, 2012;Rinke et al, 2018;Tully, 2019;Xie et al, 2018). Recently, Xie et al (2018) presented a new partially reconstructed MGIIa genome, the MGIIa_P, which contained higher proportions of glycoside hydrolases indicative of the ability to hydrolyse glycosidic bonds.…”
mentioning
confidence: 99%
“…Additionally, the Thermoplasmata, while present at abundances >1% in all size fractions and across the entire salinity gradient, was overwhelmingly dominant in the marine station on both particle sizes. The Thermoplasmata present in this station were mostly composed of Group II Euryarchaeota, an archaeal group that has been well documented in coastal marine waters (DeLong, 1992;Galand et al, 2008;Xie et al, 2018). A recent study from the Pearl River Estuary found that Group II Euryarchaeota are dominant in marine water, but not as common in brackish water (Xie et al, 2018).…”
Section: Archaeamentioning
confidence: 71%
“…The Thermoplasmata present in this station were mostly composed of Group II Euryarchaeota, an archaeal group that has been well documented in coastal marine waters (DeLong, 1992;Galand et al, 2008;Xie et al, 2018). A recent study from the Pearl River Estuary found that Group II Euryarchaeota are dominant in marine water, but not as common in brackish water (Xie et al, 2018). The increased relative abundance of the Halobacteria downstream and the dominance of Thermoplasmata in the marine station is likely related to increasing salinity, showing that in addition to anaerobic stress, salinity is an important factor in determining archaeal community composition.…”
Section: Archaeamentioning
confidence: 91%
“…Poseidoniales abundance is 10 6 -10 7 genes or cells L -1 in oligotrophic waters [62][63][64][65][66] and 10 7 -10 8 genes or cells L -1 in coastal waters [9,54,56,[67][68][69]. Greater gene abundance in inshore, nearshore, and mid-shelf waters indicates Ca.…”
Section: Abundance Of Ca Poseidoniales Genes In the South Atlantic Bmentioning
confidence: 99%